Near-surface geophysical imaging of a thermokarst pond in the discontinuous permafrost zone in Nunavik (Québec), Canada - Bussière, Léa; Schmutz, Myriam; Fortier, Richard; Lemieux, Jean-Michel; Dupuy, Alain (Permafrost and periglacial processes, 2022)
In this study, high resolution ground-penetrating radar (GPR), electrical resistivity tomography (ERT), and spectral-induced polarization tomography (SIPT) were used to (i) delineate characteristic solifluction features, (ii) map the ice distribution, and (iii) assess subsurface water content and permeability in the surrounding rampart of a thermokarst pond in the discontinuous permafrost zone. The study site is located in the Tasiapik Valley near Umiujaq in Nunavik (Québec), Canada, which benefits from decades of geological mapping, geophysical investigation, and monitoring of ground temperature and thaw subsidence, providing an extensive understanding of the cryo-hydrogeological context of the area. The results of geophysical investigation undertaken in this study were cross validated using core sampling, laboratory core analysis, and in situ ground temperature and water content monitoring. Based on this investigation, a conceptual model was derived and compared to the stratigraphy of cross-section described in literature in finer-grained context. Very good consistency was found from one in situ geophysical survey to another, as well as between the derived stratigraphic models and the ground truth. The combination of all the available data allowed the development of a detailed cryohydrogeological model across the studied thermokarst pond, which highlights the effect of lithology, topography, and land cover on the distribution and mobility of water in the ground.
Gesehen am 23.09.2025